Model Manajemen Kolaboratif Lintas Sektor dalam Meningkatkan Nilai Ekonomi Wisata Pedesaan: Studi Kasus Bengkelung Park, Kabupaten Pekalongan - Halim Ahmad (Journal of Economics, Management, and Accounting, 2025)
This study aims to analyze the effectiveness of the cross-sector collaborative management model (Pentahelix) in increasing the economic value of rural tourism in Bengkelung Park, Pekalongan Regency. The study uses a descriptive qualitative approach with data collection techniques through unstructured interviews, field observations, and documentation. The results show that collaboration between the government, academics, the private sector, the community, and the media has significantly strengthened the local economy. The government plays a role in facilitating policy and infrastructure, academics as research-based advisors, the private sector as investment partners, the community as the main driver, and the media as digital promotion agents. The implementation of the Pentahelix model increased community income by an average of 86.7%, expanded employment opportunities, and strengthened village institutional capacity through the integration of Pokdarwis and BUMDes. These results confirm that cross-sector collaborative governance is an effective strategy for strengthening the competitiveness of the rural tourism economy and promoting sustainable development based on community participation.